Solidification and fracture of an as-cast Ni alloy - Torkar, Matjaž (Materiali in tehnologije, 2006)
The investigation was carried out on samples cut from 20-kg as-cast ingots of a Ni alloy. The as-cast microstructures were examined, the intensity of the segregations were determined, and the fracture surfaces of the specimens, cooled in liquid nitrogen, were examined. It was found that with slow solidification, carbide particles precipitate on the grain boundaries, diminishing the grain-to-grain cohesion and influencing the morphology of fracture. In the areas of columnar solidification the fracture propagates along the dendrite boundaries.
Keywords: nikljeve zlitine; mikrostruktura; strjevanje